Cystatin C and risk of hip fractures in older women. (21st May 2013) - Ensrud, Kristine E; Parimi, Neeta; Cauley, Jane A; Ishani, Areef; Slinin, Yelena; Hillier, Teresa A; Taylor, Brent C; Steffes, Michael; Cummings, Steven R; ,
ABSTRACT To test the hypothesis that older women with higher cystatin C are at increased risk of hip fracture independent of traditional risk factors including hip bone mineral density (BMD), we performed a case‐cohort analysis nested in a cohort of 4709 white women attending a Year 10 (1997–1998) examination of the Study of Osteoporotic Fractures that included a random sample of 1170 women and the first 300 women with incident hip fracture occurring after Year 10 examination. Serum cystatin C and creatinine were measured in Year 10 sera. In a model adjusted for age, clinical site, body mass index, and total hip BMD, higher cystatin C was associated with an increased risk of hip fracture (p for linear trend 0.008) with women in quartile 4 having a 1.9‐fold higher risk (hazard ratio [HR] 1.91; 95% confidence interval [CI], 1.24–2.95) compared with those in quartile 1 (referent group). Further adjustment for additional risk factors only slightly attenuated the association; the risk for hip fracture was 1.7‐fold higher (HR 1.74; 95% CI, 1.11–2.72) in women in quartile 4 compared with those in quartile 1. In contrast, neither serum creatinine nor creatinine‐based estimated glomerular filtration rate (eGFRCr) were associated with risk of hip fracture. Older women with higher cystatin C, but not higher serum creatinine or lower eGFRCr, have an increased risk of hip fracture independent of traditional risk factors. These findings suggest that cystatin C may be a promising biomarker for identification of older adults at high risk of hip fracture.